A numerical model for the time-dependent wake of a pedalling cyclist. (December 2019) - Griffith, Martin D; Crouch, Timothy N; Burton, David; Sheridan, John; Brown, Nicholas AT; Thompson, Mark C
A method for computing the wake of a pedalling cyclist is detailed and assessed through comparison with experimental studies. The large-scale time-dependent turbulent flow is simulated using the Scale Adaptive Simulation approach based on the Shear Stress Transport Reynolds-averaged Navier–Stokes model. Importantly, the motion of the legs is modelled by joining the model at the hips and knees and imposing solid body rotation and translation to the lower and upper legs. Rapid distortion of the cyclist geometry during pedalling requires frequent interpolation of the flow solution onto new meshes. The impact of numerical errors, that are inherent to this remeshing technique, on the computed aerodynamic drag force is assessed. The dynamic leg simulation was successful in reproducing the oscillation in the drag force experienced by a rider over the pedalling cycle that results from variations in the large-scale wake flow structure. Aerodynamic drag and streamwise vorticity fields obtained for both static and dynamic leg simulations are compared with similar experimental results across the crank cycle. The new technique presented here for simulating pedalling leg cycling flows offers one pathway for improving the assessment of cycling aerodynamic performance compared to using isolated static leg simulations alone, a practice common in optimising the aerodynamics of cyclists through computational fluid dynamics.